Peran Rumah Qur'an Darul Mumtazin dalam Pemberdayaan Masyarakat - N, Nuarisma; Munawaroh, Siti; Sopiah, Siti; Ummah, Zalva Mu’allifatul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the role of the Darul Mumtazin Qur’an House in community empowerment in Demangan Village, Ponorogo. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results of the study showed that the Qur’anic House played a role in four main aspects: (1) strengthening of early childhood religious literacy through tahfidz, calistung, and tilawah programs; (2) economic empowerment of surrounding communities through the growth of student activity-based microenterprises; (3) socio-cultural strengthening through shared religious activities that strengthen Islamic brotherhood; and (4) the integration of Islamic values into the social life of the community. Despite facing challenges such as limitations of teaching staff, operational funds, and facilities, Darul Mumtazin’s Qur’an House continues to consistently fulfill its role as an agent of Islamic value-based empowerment. This study makes an important contribution in modeling community empowerment through faith-based non-formal educational institutions.